Perceptions in English For Academic and Professional Purposes Competencies: An Analysis of TVL Class - Herida, Irene Claire P; Enriquez, Alexis (Yayasan Sembilan Pemuda Indonesia, 2020)
This study identified the students’ perceptions in English for Academic and Professional Purposes. This study employed the descriptive research design to describe the perceptions of the respondents in the different competencies of the course on English for Academic and Professional Purposes. The researcher-made statements comprised a 5point -scale that range from always to never in identifying the perceptions. There were 15 students who participated and validated such examples were gained or not at all taught by their respective teacher. Results of the study say that, “I was taught of the language used specifically formal language in academic texts from various disciplines” has the highest (4.6) followed by the statement, “I learned to form opinions based on facts”, ( = 4.47), “I learned how to summarize the content of an academic text”, “I was taught to cite specific sources to support claims and I learned to present ideas convincingly” ( =4.4). Consequently, the statement, “Using the appropriate language for a specific discipline was taught to me” ( =4.3), “My teacher explained how to make research topics” ( =4.27), thus, the respondents positively perceived English for Academic and Professional Purposes.